Studi Kepuasan Pelanggan Terhadap Pelayanan Air Bersih Perumda Tirta Muaro Unit Teluk Singkawang - Siti Umi Kalsum; Asih Suzana; Amira Qotrunada Harahap (Universitas Batanghari Jambi, 2021)
PERUMDA Tirta Muaro Unit Teluk Singkawang in the dimension of assurance is still not good. As evidenced by the low scope of service in this unit. Marked by the number of customers in 2020 as many as 2035 people. While the population of Sumay Subdistrict in 2020 as many as 21,398 people (Tebo Regency in Numbers, 2021). This means that the service coverage is 9.5%. This has not met the government's target of drinking water services of 75% for rural areas (Permen PU No. 13, 2013).This type of research includes explorative descriptive research using qualitative statistical research techniques. This research method uses survey method with customer population of PERUMDA Tirta Muaro Unit Teluk Singkawang. Sampling techniques using slovin formula. The analysis technique uses multiple linear regression analysis, with F test and t test using SPSS software. The results of the study that the level of customer satisfaction based on respondents' responses to 5 (five) dimensions of service quality received a score of 3.54 in the category of satisfied.